Studi Komparasi Strategi Team Quiz dengan Word Square Terhadap Hasil Belajar IPA Siswa Kelas III MIN Patihan Tahun Ajaran 2015/2016 - Sari, Ariyana Kusuma (2016)
The purposeof this studyisto :(1) Know the difference between using the strategy with the strategy Word Quiz Team Square on learning outcomes third grade science students MIN Patihan the academic year 2015/2016. (2) Knowing better strategy between strategy with the strategy Word Quiz Team Square to the learning outcomes of students III MIN IPA Patihan the academic year 2015/2016. Subjects in this study were class III MIN Patihan , which consists of class III C totaling 35 students who applied strategy Quiz Team and III D totaling 35 students who applied strategies Word Square .Data collection methodsused aretests anddocumentation. Data analysis techniqueused isthe t test, whichpreviouslyperformedthe prerequisite testanalysis is thebalance testwithF test, test for normalitywith theKolmogorov-Smirnov method. Fromthe data analysiswith a significance levelof 5%can be concludedthat: (1) There are different strategies with strategies Word Quiz Team Square on learning outcomes third grade science students MIN Patihan the academic year 2015/2016. Based on t-test obtained t count> t table is 4,659> 1,995 so the hypothesis that there is a difference between the effects of the strategy with the Word Quiz Team Square on learning outcomes of the third grade science students MIN Patihan acceptable academic year 2015/2016.(2) Strategy Team Quiz better than strategy Word Square on learning outcomes third grade science students MIN Patihan the academic year 2015/2016. The average value of learning outcomes IPA III C class by using strategy and III D Quiz Team using the strategy Word Square, ie 80.14> 72.57 so the hypothesis Strategy Team Quiz better than the strategy Word Square on learning outcomes IPA class III MIN Patihan acceptable academic year 2015/2016.